In Situ Synthesis of CoMoO4 Microsphere@rGO as a Matrix for High-Performance Li-S Batteries at Room and Low Temperatures - Ronggang Zhang; Haiji Xiong; Jia Liang; Jinwei Yan; Dingrong Deng; Yi Li; Qihui Wu (Molecules)
Lithium–sulfur batteries (Li-S batteries) have attracted wide attention due to their high theoretical energy density and the low cost of sulfur cathode material. However, the poor conductivity of the sulfur cathode, the polysulfide shuttle effect, and the slow redox kinetics severely affect their cycling performance and Coulombic efficiencies, especially under low-temperature conditions, where these effects are more exacerbated. To address these issues, this study designs and synthesizes a microspherical cobalt molybdate@reduced graphene oxide (CoMoO4@rGO) composite material as the cathode material for Li-S batteries. By growing CoMoO4 nanoparticles on the rGO surface, the composite material not only provides a good conductive network but also significantly enhances the adsorption capacity to polysulfides, effectively suppressing the shuttle effect. After 100 cycles at room temperature with a current density of 1 C, the reversible specific capacity of the battery stabilizes at 805 mAh g−1. Notably, at −20 °C, the S/CoMoO4@rGO composite achieves a reversible specific capacity of 840 mAh g−1. This study demonstrates that the CoMoO4@rGO composite has significant advantages in suppressing polysulfide diffusion and expanding the working temperature range of Li-S batteries, showing great potential for applications in next-generation high-performance Li-S batteries.